Leaders and Leadership - Ecler Jaqua; Terry Jaqua (Archives of Community Medicine and Public Health - Peertechz Publications, 2021)
Leaders give others a sense of direction and represent them in various forums. Leadership has existed for decades, and different authors have tried to define the term. One such definition is that "Leadership is a relationship that involves the mobilizing, influencing and guiding of others toward desired goals" [1]. To help leaders, scholars have developed different models to identify the best leadership style tailored to different situations. There is no single best style, and a leader must consider their personality, task, and group makeup to be effective.  This paper narrates my leadership experience and examines how contingency theory and power sources can be applied to this experience.